2004
DOI: 10.1007/s00432-004-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of e-cadherin in high-risk breast cancer

Abstract: In contrast to other studies on heterogeneous populations, e-cadherin is preserved in aggressive tumors in this high-risk population. The ethnic and socio-economic risk stratification needs to be accounted for in studies correlating markers and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 18 publications
3
24
4
Order By: Relevance
“…In human breast cancer, conflicting results are also to be found in the literature. Thus, significant differences were reported by some authors (Siitonen et al, 1996;Charpin et al, 1997;Gonzalez et al, 1999;Parker et al, 2001;Cobanoglu et al, 2004) but not by others (Jones et al, 1996;Kovacs et al, 2003;Howard et al, 2005). Gamallo et al (1993) demonstrated greater immunoreactivity in grade I carcinomas than in grade II and grade III, giving support to our results.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In human breast cancer, conflicting results are also to be found in the literature. Thus, significant differences were reported by some authors (Siitonen et al, 1996;Charpin et al, 1997;Gonzalez et al, 1999;Parker et al, 2001;Cobanoglu et al, 2004) but not by others (Jones et al, 1996;Kovacs et al, 2003;Howard et al, 2005). Gamallo et al (1993) demonstrated greater immunoreactivity in grade I carcinomas than in grade II and grade III, giving support to our results.…”
Section: Discussionsupporting
confidence: 83%
“…This contrasted with some studies in human breast cancer in which either no such association was demonstrated (Charpin et al, 1997;Parker et al, 2001;Kovacs et al, 2003;Cobanoglu et al, 2004) or increased E-cadherin immunolabelling was observed as tumour size increased (Howard et al, 2005). Heimann et al (2000), however, concluded that in breast cancer there was a trend towards decreased E-cadherin expression with increased tumour size.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The remaining 26 did not meet inclusion criteria. Eighteen were excluded for study design: 11 were case series [11,[22][23][24][25][26][27][28][29][30][31], two were case-control studies [32,33] and five were cross-sectional analyses [13-15, 34, 35]. Four studies did not report on 5-year all-cause or breast cancer-specific mortality [5,10,36,37].…”
Section: Methodologic Assessmentmentioning
confidence: 99%
“…Claudin-3 and -4 are expressed at higher level in high-grade and ER- tumors, especially in BLBC [31,33]. Claudin-4, in line with E-cadherin, was found to be a biomarker predicting poor prognosis in BC [34,35]. At mRNA (derived from in silico data) and protein expression (derived from our IHC investigations) level, we have noted a discrepancy, which we suggest is the result of the following: (i) the sample number was still low, although we used all available public gene expression data sets and all available BRCAmut and BRCAwt cases from both our archives; (ii) correspondingly, the FFPE cohort could not be matched for age and hormone receptor/subtype status to the data set analyzed by bioinformatics, and (iii) epigenetic regulation may alter the translation process of the proteins investigated.…”
Section: Discussionmentioning
confidence: 99%